Informação, embalagem, música e ASMR (Autonomous Sensory Meridian Response) e sua influência na aceitação, nas emoções e nas percepções acerca de chocolate sem açúcar - Monsores, Raisa Morgado de Castro (2021)
Faced with so many options in the food market, consumers have a wide variety of products available that try to attract attention and offer healthier alternatives in order to satisfy the benefits in terms of well-being and health. There is a tendency in the area of research in sensory analysis and consumer behavior to measure emotions and understand how feelings are linked to food acceptance, after all, liking the sensory properties of a food is not enough to explain the choice for a product. Through the nonsensory characteristics of packaging, information, ASMR (Autonomous Meridian Sensory Response) and music, this study aimed to test their possible influence on consumer acceptance and emotions and on the perceptions about sugar-free milk chocolate in an “umbrella format” in a distance study, using the Focus Group methodology, acceptance analysis, emotions through the emoji and RATA (Rate-allthat-apply) scale, testing two age groups: 20 to 29 years and 30 to 45 years. Through the focus group, the opinion of the participants was collected to compose the product concept. In the acceptance analysis, there was no significant difference between the attributes when comparing the age groups, only a significant difference when comparing the sessions within the same age group. The same happened for the analysis of emotions, as it was possible to perceive through the emojis the increase in positive facial expressions throughout the sessions that were studied: information, packaging, music and ASMR and greater consumer x product interface For RATA analysis, there were several terms that showed a significant difference when compared between session 1 (blind) and session 2 (with non-sensory attributes involved). All the data corroborate to conclude that it is possible to improve the acceptance, the consumer x product interface through the analysis of emotions and to position a product in the market in an assertive way exploring the non-sensory resources available in a virtual way in order to offer the consumer a good consumption experience.